Impacts of stress-induced inflammation on feed intake of beef cattle - Gouvêa, Vinícius N.; Cooke, Reinaldo F.; Marques, Rodrigo S. (Frontiers in Animal Science, 2022)
Livestock animals are constantly exposed to unavoidable stressful situations during their productive life that triggers stress-induced inflammatory responses, which are known to influence their nutrient requirements and feed intake. Decreased growth performance and immunocompetence of stressed livestock are often the main consequence of reduced feed intake. Because feed intake is usually reduced in animals experiencing stress conditions, concentrations of certain nutrients in the diets typically need to be increased to meet the requirements of the animals. Therefore, understanding the mechanisms that control feed intake in animals experiencing stress-induced inflammation is the bottom line for increasing intake, milk or meat production, feed efficiency, and animal health. This review highlights the hormones regulating feed intake in ruminants and how stress-induced inflammation affect these hormones at local and systemic levels. The mechanism of feed intake regulation in ruminants is extremely complex and involves multiple controls. It is well known that the liver is the primary sensor of energy status in animals under homeostatic conditions, which transmits signals to brain feeding centers that modulate appetite. The physiologic consequences associated with different stressors will result in diverse mechanisms controlling feed intake than those observed in animals under homeostatic conditions. It is suggested that the immune system can interact with the central nervous system to modulate feed intake. As example, stress events elicit numerous stressors that increase circulating proinflammatory cytokines, including tumor necrosis factor-alpha (TNF-α), interleukin-6 (IL-6), and IL-8, and acute-phase proteins (APP), and the magnitude of these responses are negatively correlated with feed intake. A direct effect of these cytokines on rumen microbial fermentation and intestinal barrier function was also reported and might indirectly affect intake regulation in ruminants. This review describes the main hormones and proinflammatory cytokines involved in stress-induced inflammation and how they can directly or indirectly affect intake regulation in ruminants. Understanding the mechanisms controlling feed intake in ruminants will help producers to implement management and feed strategies to optimize productivity and profitability in stressed livestock species.